Scars Beyond Skin: A Socio-Legal Study On Acid Attack Survivors In India - Ahuja, Ridima (Trinity Law Review, 2026)
Acid violence is not just an attack on the body; it is an attempt to silence and erase a woman’s identity.Laxmi Agarwal, Acid Attack Survivor & Activist (BBC Inter view, 2018).The brave survivor Laxmi Agarwal, in her interview, stated the immense psychological impact of acid violence on the mind and physical body of a woman. The acid attack is a crime against women’s identity, giving scars that impact the mind and health of women. The wounds of the attack are not just physical. Still, they are evidence for a deeply rooted patriarchy in society. The statistics explain the nev er-ending emerging cases, With An inverse proportion of increasing Crime rate of acid violence, with respect to decreasing conviction rates, Which Impacts Society as a whole, making it Unsafe For its people and affecting their human rights.
Keywords: Gender Based Vi olence; Society; Social Impact; Acid Attack; Survivors; Psychology